(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The marine soil and sediment samples were collected from different locations of mangrove forest Sundarbans, Bangladesh the largest tidal halophytic mangrove forest in the world. A total of twenty nine Actinomycete strains (AIAH-1 to AIAH-29) were isolated by serial dilution method using isolation media. Among twenty nine strains, AIAH-10 was selected for further study due to its potent antibacterial activity against a wide range of pathogenic bacterial strains. On the basis of morphological, cultural and biochemical studies, the strain AIAH-10 was assigned to Streptomyces sp. The present study was designed to investigate the in vitro insecticidal and time-kill profile of ethyl acetate extracts of marine Streptomyces sp. A dose dependent mortality was observed against the larvae of Sitophilus oryzae. The larval mortality was recorded as 100% in the concentration of 80 mg/ml and higher concentrations, LC50 was found as 11.48 mg/ml. The minimum inhibitory concentration was recorded as 8 to 32 mg/ml against six different pathogenic bacterial strains. Average Log10 reductions in viable cell counts for the extracts ranged from 1.91 Log10 and 2.86 Log10 cfu/mL after 3 h interaction and 2.10 Log10 and 2.93 Log10 after 6 h interaction at MIC, 2 × MIC, 3 × MIC and 4 × MIC concentrations. This investigation reveals that the Streptomyces species isolated from Sundarbans, Bangladesh may be interesting source for the isolation of potent bioactive compounds. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22332 Bangladesh Pharmaceutical Journal 17(2): 151-156, 2014